Does a stoma reduce the risk of anastomotic leak and need for re-operation following low anterior resection for rectal cancer: systematic review and meta-analysis of randomized controlled trials - Phan, Kevin (J Gastrointest Oncol, 2019)
BACKGROUND: There is a relatively high risk of anastomotic leak in low anterior resection (LAR), associated with significant morbidity and mortality. This systematic review and meta-analysis aims to compare diverting stoma vs. no stoma for LAR in terms of leak rates, reoperations, mortality rates and complication rates. METHODS: We systematically performed electronic searches of databases Ovid Medline, PubMed, CCTR, CDSR, ACP Journal Club and DARE from inception to present. Only randomized controlled trials comparing LAR for rectal cancer with versus without stoma diversion were included for analysis. Main outcomes were anastomotic leak, reoperation rate and mortality. Secondary outcomes included other operative and stoma-related complications. RESULTS: Eight randomized controlled trials were included in the study for qualitative and quantitative analyses. A significantly longer operative duration for patients with stoma diversion was seen (WMD 19.50 min; 95% CI: 7.38, 31.63; I(2)=0%, P=0.002). The pooled rate for anastomotic leak was significantly lower for those with stoma diversion (6.3% vs. 18.3%; RR 0.36; 95% CI: 0.24, 0.54; I(2)=0%; P<0.00001). There was lower reoperation rate for patients with stoma diversion compared to no stoma (5.9% vs. 16.7%; RR 0.40; 95% CI: 0.26, 0.60; I(2)=0%; P<0.00001). No significant difference was found in terms of leak-related mortality between stoma vs. no-stoma cohorts (0.47% vs. 1.0%; P=0.51). CONCLUSIONS: The present meta-analysis suggests a diverting or defunctioning stoma following LAR for rectal cancers can reduce anastomotic leak and reoperation rates, without increased risk of mortality or other complications.